Identifikasi Telur Cacing Sth Dengan Menggunakan Pewarna Alami Ekstrak Antosianin Dari Buah Naga - Arwie, Dzikra; Islawati, Islawati; Salnus, Subakir (Jurnal Medisains Kesehatan, 2024)
Soil Transmitted Helminths (STH) are a group of worms that require specific soil conditions to reach the infective stage in their life cycle. These worms can infect humans through various means, all involving contact with soil contaminated by worm eggs or larvae. Qualitative testing for worm eggs that infect humans generally uses microscopic fecal examination in laboratories. Staining is often used to enhance the contrast and visibility of the eggs, with common stains including eosin, Lugol's iodine, safranin, and methylene blue. However, these stains have negative effects on both humans and the environment. Therefore, it is necessary to develop a safer natural staining product for humans and the environment, such as anthocyanin extract. Anthocyanin is a pigment that ranges in color from red to blue and is widely found in plants. These pigments are classified as flavonoid pigments. Flavonoid compounds, including anthocyanins, are polar and can be extracted using polar solvents. This study aims to optimize the use of dragon fruit anthocyanin as a staining agent in STH examination. The research was conducted using a categorical descriptive laboratory observation method, with positive fecal samples analyzed using sedimentation at various concentrations: 100%, 80%, 60%, 40%, and 20%. The results showed that dragon fruit anthocyanin extract at an 80% concentration could be used as an alternative to 2% eosin in staining worm eggs. The conclusion is that dragon fruit anthocyanin extract at concentrations of 20% to 80% is effective as a stain for identifying STH eggs.